Ultrastructural and immunocytochemical features of the epidermis of the lizard Heloderma suspectum indicate richness in lipids and lack of a specialized shedding complex. (31st October 2011) - Alibardi, Lorenzo; DeNardo, D. F.
<x xml:space="preserve">Abstract</x> Alibardi, L. and DeNardo, D.F. 2011. Ultrastructural and immunocytochemical features of the epidermis of the lizard Heloderma suspectum indicate richness in lipids and lack of a specialized shedding complex. —Acta Zoologica (Stockholm) 00: 1–9. Abstract The epidermis of the venomous lizard Heloderma suspectum has been studied for detecting generalized and desert adaptations. A thick and non‐completely syncytial beta‐keratin layer is followed by 60–90 layers of mesos‐cells. Non‐lamellated or sparse lamellated lipid material is seen among mesos‐cells where lipids form the main barrier against water loss. The alpha‐layer is made of interlocking cells with irregular perimeter that are connected through desmosomal remnants. Immunocytochemistry shows that beta‐keratin is present in beta‐cells, disappears in mesos‐cells but is diffuse in alpha‐cells. Alpha‐keratin is seen in mesos‐cells but lowers in alpha‐cells where alpha‐keratin probably mixes with beta‐keratin. Although the sequence of layers formed during the renewal stage of the epidermis was not available, a specialized shedding layer with an outer oberhautchen faced to an inner clear layer appears absent in this species. This condition suggests that shedding occurs at the boundary between the outer (old) alpha‐layer and the inner (new) beta‐layer formed underneath the alpha‐layer. The thick mesos layer is likely an efficient adaptation to limit water loss in desert conditions while the poorly specialized shedding complex may suggest a primitive stage in the evolution of the shedding layer in this lizard or a special adaptation to water shortage.